STUDENTS’ RESPONSES TOWARD INDIRECT FEEDBACK THROUGH ASYNCHRONOUS ONLINE MEDIA - Fahmi Hidayat (Vidya Karya, 2018)
Abstract. This study investigated students’ responses toward indirect feedback in asynchronous online media. The study aimed to provide evidence that the students gained more interest and confidence after getting indirect feedback from teacher and writing by using technology. The study used qualitative approach. The study involved 20 students whereas students have to write a paragraph. The data were collected by using three types of instruments including writing test, assessment format, and questionnaire. The study resulted in the following findings; students in this study were successful in correcting their errors and improving their writings after the teacher gave indirect feedbacks for their paragraph. However, the students’ writing requires improvement since the same problems and even the new problems were still found in students’ after getting indirect feedback. Students need to enrich their vocabulary to describe their thought. Students rarely use the punctuation in their sentences. Keywords: writing, indirect feedback, asynchronous online.